Sprint acceleration. Its importance and application from blocks (Coaching Track & Field Athletics)
Sprint acceleration is a skill that is required by all track and field events. The only thing that changes is the positions from which the athlete accelerates. Development of acceleration is therefore an important phase of sprinting for all track and field athletes.